PEMANFAATAN UBI JALAR PADA PEMBUATAN CHEESE CAKE SEBAGAI OPTIMALISASI BAHAN PANGAN LOKAL - Rattikah Fitrianty (JURNAL MANAJEMEN KULINER, 2024)
Cheese cake is a type of dessert that has high interest among the public because it has a soft, tasty and light taste and texture when eaten. Apart from that, it is also easy to produce yourself industrially or at home because the ingredients are easy to obtain and process. Making cheese cake is fast. However, different from existing products on the market, the product that will be developed this time is cheese cake with the substitution of wheat flour as the main ingredient for sweet potato flour. In the future, it is hoped that this product can become one of the innovations for several cheese cake variants so that it has value or added value even though it uses local food ingredients so that it can help local farmers and communities producing sweet potato flour in order to improve the regional economy so that it can produce contemporary products that are in demand by the general public but has high taste and competitiveness. This sweet potato cheese cake is made by substituting sweet potato as the main ingredient, namely sweet potato flour for the basic dough. Then other core ingredients are added, namely cheese cream, whipped cream or heavy cream, butter, vanilla, salt, milk and egg yolks, accompanied by garnishes or decorations that are suitable for the aesthetics of the desired product. Based on research using the R&D (Research & Development) method, the cheesecake product was developed into a ratio of 50, 75 and 100 with sweet potato flour as a substitute. By carrying out organoleptic testing on 30 sample panelists with a Likert scale of 1 sd 5. The research results obtained an average value for all reference products of 1 and 3 for development products. This shows a very significant and high value for product development, and this innovative product of sweet potato substitute cheese cake has great potential and can be accepted by the public in terms of taste, aroma, texture and color. And it can be used as a snack that is rich in nutrition and nutrients